PERLINDUNGAN HUKUM TERHADAP ARTIS SEBAGAI KORBAN TINDAK PIDANA CYBERBULLYING PADA MEDIA SOSIAL INSTAGRAM DI INDONESIA - Cintyadewi Permana, Kadek; Ariawan, I Gusti Ketut; Dike Widhiyaastuti, I Gusti Agung Ayu (Kertha Wicara : Journal Ilmu Hukum; Vol. 05, No. 06, November 2016, 2016)
This thesis entitled "Legal Protection Against Artist as Victims of Crime Cyberbullying On Social Media Instagram in Indonesia". The research problems are criminal acts of the criminal policy of cyberbullying on instagram social media in Indonesia and legal protection for victims of crime of cyberbullying on instagram social media in Indonesia. The method used is a normative legal research moved from the vacuum of legal norms relating to this study. The conclusion of this study is the crime of cyberbullying arrangements contained in the Penal Code as well as the ITE Law, only those settings to snare the perpetrators only, while arrangements regarding legal protection can be given to victims of crime of cyberbullying is not regulated in legislation in Indonesia. Criminal policy criminal acts of cyberbullying have been discussed in the Draft Bill, it's just that there are still some deficiencies.
Keywords: Kebijakan Hukum Pidana, Korban, Cyberbullying